Level of quality of service center of languages of Callao National of applying the model SERVQUAL - Suárez Bazalar, Raúl (2016)
The results of research on measuring the level of quality by Servqual model in the Language Centre of the National University of Callao (CIUNAC) are presented. Users’ perceptions regarding the services provided by the CIUNAC and set the level of service quality were determined. Overall there is a median satisfaction with the quality of service offered by the Language Centre, being the least satisfaction with the counseling procedures.The model used will help establish improvement plans for each area of student interest, improving quality of service in order to be a competitive organization.